Geographic Influence and Metabolomics-Driven Discovery of 5-Alpha Reductase Inhibitors in Tectona grandis L.f. (Teak) Leaves - Nutchaninad Tanuphol; Corine Girard; Prapapan Temkitthawon; Nungruthai Suphrom; Nitra Nuengchamnong; Tongchai Saesong; Kamonlak Insumrong; Abdulaziz Wadeng; Wiyada Khangkhachit; Andy Zedet; Ratchadaree Intayot; Siriporn Jungsuttiwong; et al. (Molecules)
The inhibition of steroid 5-alpha reductase (S5AR), a key mechanism for managing dihydrotestosterone-dependent conditions, has been demonstrated in teak (Tectona grandis L.f.) leaf extracts. Our recent clinical study confirmed the effectiveness of a hair growth formulation containing teak leaf extract in males with androgenic alopecia. However, significant variability in S5AR inhibitory activity among teak leaf samples from different regions underscores the need for quality control of raw materials. This study applied a metabolomics approach to investigate the influence of leaf age, harvesting period, and geographic origin on chemical composition and S5AR inhibitory activity, as well as to identify active S5AR inhibitors. Geographic origin emerged as the primary determinant of variations in chemical profiles and S5AR inhibitory activity. Using orthogonal partial least squares analysis, six diterpenoid S5AR inhibitors were identified, including four compounds reported for the first time as S5AR inhibitors: rhinocerotinoic acid, 7-oxo-8-labden-15-oic acid, 8-hydroxy-labd-13-en-15-oic acid, and a novel diterpene, 7-hydroxy-labd-8,13-dien-15-oic acid. These findings highlight the potential of metabolomics as a powerful tool for discovering bioactive compounds and optimizing raw material selection. By prioritizing proven geographic sources, consistent bioactivity can be achieved, supporting the therapeutic potential of teak leaves in managing S5AR-related conditions.